Entrepreneurship at the Periphery: Exploring Framework Conditions in Core and Peripheral Locations. (July 2013) - Felzensztein, Christian; Gimmon, Eli; Aqueveque, Claudio
This paper reports the findings of the first academic study in Latin America, and one of the few in any emerging economy, to explore entrepreneurial perceptions and activity in peripheral geographic locations. A survey of experts included 139 respondents from three peripheral regions and two core regions in Chile. A key finding is that those located at the periphery perceived critical entrepreneurial resources and access to markets less favorably than their counterparts at the core, but surprisingly, they perceived greater business opportunity in their area. A further survey of 2, 200 respondents concerning actual entrepreneurial activities among the total adult population revealed no differences between peripheral and core regions. This study revives the debate about specific regional policies for fostering the growth of local business, and the entrepreneurial framework conditions required at the regional level in emerging economies.